The Role of Work Involvement in The Influence of Organizational Culture and Transformational Leadership Style on Employee Performance in The Government of Riau Islands Province - Muhammad Fadliansyah; Agustinus Setyawan (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
The quality of human resources plays a significant and crucial role as an organizational identity in determining success in achieving objectives. However, some employees still lack the expected performance standards. Organizational culture is a primary factor influencing this issue, further exacerbated by the prevalence of unhealthy cultural practices and variations in background, level, and group dynamics. These factors contribute to a lack of employee ownership and commitment to their organization. This study seeks to explore the impact of organizational culture and transformational leadership style on employee performance within the Riau Islands Provincial Government, with work involvement serving as a mediating variable. The research employs a quantitative approach, with a population of 350 civil servants. The study’s findings indicate a direct, positive, and significant correlation between organizational culture, transformational leadership style, and employee performance. Moreover, when considered together, organizational culture, transformational leadership style, and work involvement have a positive and significant impact on employee performance